2018
DOI: 10.1038/s41598-018-22866-w
|View full text |Cite
|
Sign up to set email alerts
|

Burst mode pumping: A new mechanism of drinking in mosquitoes

Abstract: Mosquitoes transport liquid foods into the body using two muscular pumps in the head. In normal drinking, these pumps reciprocate in a stereotyped pattern of oscillation, with a high frequency but small stroke volume. Do mosquitoes modulate their neuromotor programs for pumping to produce different drinking modes? More broadly, what are the mechanical consequences of a two-pump system in insects? To address these questions, we used synchrotron x-ray imaging and fluid mechanical modeling to investigate drinking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 34 publications
3
11
0
Order By: Relevance
“…These studies show that, indeed, the pumps are sequentially coordinated; the cibarial and pharyngeal pumps fire nearly at the same time, but with a small phase lag (Kim et al 2011(Kim et al , 2012(Kim et al , 2013. The most recent work (Kikuchi et al 2018) demonstrated that there are two types of pumping: continuous pumping, in which the cibarial pump performs most of the work, and burst-mode pumping, in which the pharyngeal pump does most of the work. Furthermore, in continuous feeding, the cibarial pump does not expand to its greatest possible extent, and is acting as a pass-through to the pharyngeal pump (Kim et al 2013, Kikuchi et al 2018).…”
Section: Family Lmentioning
confidence: 89%
See 4 more Smart Citations
“…These studies show that, indeed, the pumps are sequentially coordinated; the cibarial and pharyngeal pumps fire nearly at the same time, but with a small phase lag (Kim et al 2011(Kim et al , 2012(Kim et al , 2013. The most recent work (Kikuchi et al 2018) demonstrated that there are two types of pumping: continuous pumping, in which the cibarial pump performs most of the work, and burst-mode pumping, in which the pharyngeal pump does most of the work. Furthermore, in continuous feeding, the cibarial pump does not expand to its greatest possible extent, and is acting as a pass-through to the pharyngeal pump (Kim et al 2013, Kikuchi et al 2018).…”
Section: Family Lmentioning
confidence: 89%
“…The most recent work (Kikuchi et al 2018) demonstrated that there are two types of pumping: continuous pumping, in which the cibarial pump performs most of the work, and burst-mode pumping, in which the pharyngeal pump does most of the work. Furthermore, in continuous feeding, the cibarial pump does not expand to its greatest possible extent, and is acting as a pass-through to the pharyngeal pump (Kim et al 2013, Kikuchi et al 2018). In burst-mode feeding, both pumps are expanded to their fullest extent.…”
Section: Family Lmentioning
confidence: 99%
See 3 more Smart Citations